Effectiveness of the advanced stop line for motorcycles in Bucaramanga validated by means of a logistic regression model - Francisco Javier León; Miguel Pérez-Pulido; Omar Mogollón-Alaguna; Miller Salas-Rondón (AiBi Revista de Investigación, Administración e Ingeniería)
Road traffic accidents are a significant public health concern worldwide, and it is essential that individual countries adopt distinct safety measures to safeguard vulnerable road users. The objective is to analyze traffic accidents occurring at Motorcycle Advanced Stop Lines by applying a Logistic Regression model. When a traffic accident occurs, a motorcycle is involved and is 15 times more likely to be of high severity compared to accidents with other road users. The implementation of this initiative requires political will. Furthermore, technical studies should support to regulate horizontal and vertical signage, which can be included in Colombia's road signage manual in the future.